Peer Support: The Key to Student Engagement at Al Wasilah Lemo Islamic Boarding School - Syam, Zaahirah; ., Ahkam; Akmal, Nur (Polteknik Ilmu Pemasyarakatan, 2025)
This study aims to determine the role of peer social support in student engagement in Islamic boarding schools. The respondents in this study were 200 male and female students of Al Wasilah Lemo Islamic Boarding School. The sampling technique used was simple random sampling. The item correlation of peer social support variables ranged from -0.09 to 0.13. The item correlation of student engagement variables ranged from 0.03 to 0.29. In the peer social support variable, the CFI value was 0.950, TLI was 0.924, and RMSEA was 0.0532. In the student engagement variable, the CFI value was 0.980, TLI was 0.960, and RMSEA was 0.0595. The reliability coefficient values of the peer social support scale were 0.834 and the student engagement scale was 0.831. The researcher found a positive correlation (0.144) between peer social support and student engagement, with significance at p=0.043 (p<0.05), indicating a significant influence. The results of the analysis also showed an R square value of 0.020. This value shows that the contribution of peer social support to student engagement is 2%. Additional analysis showed a significant difference in student engagement based on gender, with female students showing higher engagement (mean=24.8) than male students (mean=22.6). This study is expected to provide information, increase insight, and provide positive benefits especially related to peer social support and student engagement.